Occurrence of Phoma Blight Caused by Phoma destructiva on tomato (Solanum lycopersicum) in Malaysia - Rashid, Tavga Sulaiman; Sijam, Kamaruzaman; Nasehi, Abbas; Kadir, Jugah; Mohd Saud, Halimi; Awla, Hayman Kakakhan (American Phytopathological Society, 2016)
In May 2013, tomato plants cultivated in the Cameron Highlands, Pahang, Malaysia, had extensive fruit, stem and leaf spots. In severe cases, disease incidence reached 70% in glasshouses. Leaf lesions were initially small (1-2 mm), black on either surface enlarging to 1-2 cm in diameter, irregular to round in shape and slightly sunken and zonate. Stem lesions were longer, but were similar in appearance. Fruit lesions were sunken black spots of variable size at sites of wounds, insect punctures or stem scar cracks. The causal pathogen was identified as Phoma destructiva based on morphological, genetic (ITS and PCR) and pathogenicity analyses. This is thought to be the first report of Phoma blight caused by P. destructiva on tomato in Malaysia.